Lightweight Secure Directed Diffusion for Wireless Sensor Networks. (17th April 2014) - Wang, Eric Ke; Ye, Yuming; Xu, Xiaofei
We propose a lightweight secure routing scheme for wireless sensor networks, which provides authenticity and integrity in the routing process with relative low overhead by extending directed diffusion protocol with secure measures. We analyze the security capabilities and performance of our scheme; besides, we execute a simulation and the performance results are encouraging.